KARYA SASTRA SEBAGAI MEDIA REVOLUSI MENTAL (Literature Work as Mental Revolution Media) - Sabriah Razak (Balai Bahasa Sulawesi Selatan, 2014)
This writing is aimed to describe literature work which can be used as media of mental revolution. Method usedis descriptive-qualitative supported by listening and recording technique. The result shows that the folkloremay give clear description and take effect on the mental formation of the personal and school children. Thestories of Dayya and Basse Pannawa-nawa show that women have the same right as men in some cases,women should have the patience, respecting husband for the sake of happiness together. In addition, basicallywomen are intelligent, astute in politics, but do not take advantage of others who can make defamation andprejudices absurd.